Towards a Theology of the land, population and conflicts according to Fr. Las Casas: Between two commemorations: "is and is not" Las Casas in A.L. - Lassegue, Juan Bautista (1974)
In this year 1974, the 5th centenary of the birth of Fr. Las Casas (1474-1566) is commemorated. The Board of Trustees of said commemoration has its headquarters in Chiapas (Mexico); of that diocese, Las Casas was the first Bishop; his performance in it during the brief stay of about 14 months is part of a long fight for justice, before Las Casas was appointed bishop and after he resigned from that position. After Spain celebrated the fourth centenary of Las Casas's death in 1966, Latin America had the commemoration of his birth. But each town commemorates according to its "experiential dwelling", as Américo Castro says.